Evidence for Cultivation of Sesame in the Ancient World - Bedigian, Dorothea (1986)
The New York Botanical Garden; Part of the Ph.D. dissertation submitted by D. Bedigian, Department of Agronomy, University of Illinois, Urbana-Champaign, IL. References for šamaššamm? and šamnu from galley proofs CAD Š. Proposes p. 141-143 a Dravidian ety